Upper gastrointestinal carcinoid tumors incidentally found by endoscopic examinations - Chuah, Seng-Kee (World J Gastroenterol, 2005)
AIM: This study shares Asian clinical experiences of carcinoid tumors that originated in the upper gastrointestinal tract. METHODS: From May 1987 to June 2002, we had found only 13 cases of histologically confirmed carcinoid tumors in the upper gastrointestinal tract by endoscopic examinations. There were eight males and five females. The mean age was 53.16±20.51 years that ranged from 26 to 82 years. Each of their clinical presentations, locations, tumor morphology, and size and the treatment outcome were analyzed and discussed. RESULTS: One patient had a polypoid lesion at the lower esophagus, nine were stomach lesions and three located at the duodenum. All patients with polypoid and submucosal tumor types were of small size (<1.7 cm) and all patients survived after simple excision or polypectomy. Four of the five patients in tumor mass forms died and the tumors were more than 2.0 cm in size. CONCLUSION: Carcinoid tumors rarely originated from the upper gastrointestinal tract and are usually found accidentally after endoscopic study. Bigger size (more than 2 cm) tumor masses may indicate a more severe disease and poor prognosis.